INFLUENCE OF PARTIAL SUBSTITUTION OF SODIUM CHORIDE BY POTASSIUM CHLORIDE IN CABBAGE FERMENTATION - Monteiro, Paulo (Boletim do Centro de Pesquisa de Processamento de Alimentos, 2020)
This study aimed to evaluate the influence of NaCl by KCl replacement in sauerkraut physicochemical, microbiological and sensory characteristics. The partial substitution of NaCI by KCI was effective in reducing the pH throughout the fermentation, where all samples had final pH below 4.5. The sauerkraut lactic acid percentage gradually increased until stabilization, with no significant difference between treatments from the fourth day of fermentation. It was observed that in the evaluated conditions, NaCl and KCl were effective in reducing coliforms at 35°C, where from the eighth day of fermentation, a count of < 0.3 MPN.mL-1 was detected. The lactic acid bacteria count increased by 3 log cycles until the eighth day and then reduced by up to 2 log cycles until the end of the process, where no significant difference was observed. In sensory evaluation there was not a significant difference for sauerkraut color, flavor and texture parameters. According to these results we can conclude that the partial replacement of NaCl by KCl in the sauerkraut production did not alter the physicochemical and microbiological characteristics, and does not have negative influence on the product sensory characteristics.